2003
DOI: 10.1089/107999003322485107
|View full text |Cite
|
Sign up to set email alerts
|

Atlantic Salmon Interferon Genes: Cloning, Sequence Analysis, Expression, and Biological Activity

Abstract: In this work, we report cDNA cloning of two type I interferons (IFNs) from the head kidney of Atlantic salmon, called SasaIFN-alpha1 (829 bp) and SasaIFN-alpha2 (1290 bp). Both translate into 175 amino acid precursor molecules showing 95% amino acid sequence identity. The precursors have a putative 23 amino acid signal peptide, which suggests that the mature Atlantic salmon IFNs contain 152 amino acids (18.2 kDa). Salmon IFN appears to have five alpha-helices, similar to mammalian and avian type I IFNs, and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
175
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(183 citation statements)
references
References 38 publications
6
175
1
1
Order By: Relevance
“…Type I IFNs have been identified in zebrafish, Atlantic salmon, grass carp, and Fugurubripes, which several of them display similar activities to their mammal homologs (Altmann et al, 2003;Robertsen et al, 2003). IFNβ is hypothesized to have arisen from birds, and the other type I IFNs are present only in mammals (Sick et al, 1996).IFNζ, also known as limitin, was discovered for its abi lity to arrest the growth of or kill lympho-hematopo ietic cells, and is thought to only exist in mice (Oritani et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Type I IFNs have been identified in zebrafish, Atlantic salmon, grass carp, and Fugurubripes, which several of them display similar activities to their mammal homologs (Altmann et al, 2003;Robertsen et al, 2003). IFNβ is hypothesized to have arisen from birds, and the other type I IFNs are present only in mammals (Sick et al, 1996).IFNζ, also known as limitin, was discovered for its abi lity to arrest the growth of or kill lympho-hematopo ietic cells, and is thought to only exist in mice (Oritani et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Recently virusinduced IFN genes have been characterized in various fish species (Aggad et al, 2009;Altmann et al, 2003;Long et al, 2004;Lutfalla et al, 2003;Robertsen et al, 2003;Zou et al, 2007), and some downstream ISG counterparts have also been identified (Robertsen, 2006;Zhang et al, 2007), strongly indicating that teleost fish possess an IFN antiviral system. In support of this notion, IFN inducible genes including Mx and PKR have been proved to block virus replication in fish (Caipang et al, 2003;Larsen et al, 2004;Zhu et al, 2008), and there exists a conserved RLR (RIG-I-like receptors) pathway responsible for fish IFN induction during virus infection (Biacchesi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In support of this notion, IFN inducible genes including Mx and PKR have been proved to block virus replication in fish (Caipang et al, 2003;Larsen et al, 2004;Zhu et al, 2008), and there exists a conserved RLR (RIG-I-like receptors) pathway responsible for fish IFN induction during virus infection (Biacchesi et al, 2009). Fish virus-induced IFNs exhibit more homology to mammalian type I IFN molecules on the basis of protein sequence identity, but they are not clearly an ␣-or ␤-IFN (Robertsen, 2006;Robertsen et al, 2003). However, the genome structure analysis shows that these IFN molecules are more evolutionally similar to type III IFN due to the presence of introns (Lutfalla et al, 2003) and, importantly, no intronless IFN gene has been reported in fish to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the DBD, IRF family members bind to a similar DNA motif, termed interferon stimulating response element (ISRE) and IFN regulatory element (IRF-E) (Tanaka et al, 1993;Darnell et al, 1994). In teleosts, IFN molecules have been cloned and characterized from zebrafish (Danio rerio), pufferfish (Tetraodon nigroviridis), atlantic salmon (Salmo salar) and channel catfish (Ictalurus punctatus) since 2003 (Altmann et al, 2003;Robertsen et al, 2003;Long et al, 2004;Igawa et al, 2006). ISGs and their promoters were identified in rainbow trout (Oncorhynchus mykiss) Mx1 and Vig-2, Goldfish (Carassius auratus) and Atlantic cod (Gadus morhua) ISG15 (Collet and Secombes, 2001;Boudinot et al, 2001;Liu et al, 2002;Seppola et al, 2007).…”
Section: Introductionmentioning
confidence: 99%